Global Roadkill Data: a dataset on terrestrial vertebrate mortality caused by collision with vehicles - Grilo, Clara; Neves, Tomé; Bates, Jennifer; le Roux, Aliza; Medrano-Vizcaíno, Pablo; Quaranta, Mattia; Silva, Inês; Soanes, Kylie; Wang, Yun; Abate, Sergio Damián; D’ Abra, Fernanda (Nature Research, 2025)
Roadkill is widely recognized as one of the primary negative effects of roads on many wildlife species and also has socioeconomic impacts when they result in accidents. A comprehensive dataset of roadkill locations is essential to evaluate the factors contributing to roadkill risk and to enhance our comprehension of its impact on wildlife populations and socioeconomic dimensions. We undertook a compilation of roadkill records, encompassing both published and unpublished data gathered from road surveys or opportunistic sources. GLOBAL ROADKILL DATA includes 208,570 roadkill records of terrestrial vertebrates from 54 countries across six continents, encompassing data collected between 1971 and 2024. This dataset serves to minimise the collection of redundant data and acts as a valuable resource for local and macro scale analysis regarding rates of roadkill, road- and landscape-related features associated with risk of roadkill, vulnerability of species to road traffic, and populations at risk of local extinction. The objective of this dataset is to promote scientific progress in infrastructure ecology and terrestrial vertebrate conservation while limiting the socio-economic costs.